Diagnóstico preliminar sobre etnoconocimiento de la cría de abejas nativas amazónicas en la microcuenca del río Momón. Punchana. Loreto. 2022 - Sevillano Daza, Kathya Elizabeth (2022)
The study was called, preliminary diagnosis on ethno-knowledge of the breeding of native Amazonian bees in the Momón river micro-basin. Punchana. Loreto. 2021. Its objectives were: Evaluate the knowledge about native Amazonian bees and honey production, of the inhabitants of 2 communities in the Momón river micro-watershed. The non-experimental research designation was used. The research work is descriptive-transversal. There was a simple probabilistic sample of 20 people, 10 per community with experience in honey extraction. The conclusions that were reached with the work were: On the traditional knowledge of the breeding of native bees, these people have high knowledge (40%) to regular (40%), of the same; they classify the bees with simple names, those that have a sting and sting and others that are the opposite, whose development habitat is in the trunks of trees, bushes and on the ground or at the foot of trees and feed on juices or nectars and pollen from plant species for honey production (100%). They refer that their reproduction is sexual, between the queen and the drones and they make seasonal movements in search of food, which they obtain from fruit and forest species, bread crops and ornamental flowers (100%). They can extract from 20 to 25 kg of honey annually from a hive located in the natural environment. They also consider that the number of beehives in the area is decreasing, due to deforestation and climate change. The breeding of bees in family gardens and the planting of different plant species should be proposed in the same area.